Penerapan strategi digital marketing untuk UMKM Desa Dadiharja Kecamatan Rajagaluh Kabupaten Ciamis - Wely Hadi Gunawan; Rina Masruroh; Winda Oktaviani (Universitas Insan Cendekia Mandiri, 2026)
This community service program was implemented to enhance the ability of micro, small, and medium enterprises (MSMEs) in Dadiharja Village, Rajagaluh District, Ciamis Regency to apply digital marketing strategies suited to the demands of the modern economic era. The program used training sessions, hands-on practice, and mentoring, focusing on social media utilization, promotional content creation, marketplace introduction, and brand identity development. Participants included village government officials and local residents, with approximately 30 individuals taking part in the program, The results show a notable improvement in participants’ digital understanding and skills. MSMEs began managing business accounts, creating promotional content independently, and applying marketing strategies relevant to market needs. This program produced positive impacts, including increased digital literacy, wider product market reach, and stronger local business competitiveness. The activity is highly relevant to the issues faced by the community, particularly low digital literacy and limited access to modern marketing channels. This program provides practical implications in the form of enhanced capacity of rural MSME actors in utilizing digital media for product marketing, strengthened technology-based business management skills, and the establishment of a mentoring model that can be replicated in other villages with similar characteristics to promote local economic sustainability.